(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
This study is aimed to assess the mechanical and physical properties of waterlogging Acacia nilotica (babla). The important physical and mechanical properties were determined. The oven dry density of the wood of waterlogged tree and non-waterlogged tree was 780 and 850kg/m3. The MOR of the wood of waterlogged tree was 117N/mm2 while non-waterlogged tree showed the value of MOR 127N/mm2. The MOE of the wood of waterlogged tree and non-waterlogged tree was 1880 and 1950 N/mm2 respectively. The study of properties on A. nilotica wood grown in different conditions will help to choose the right type of its wood for suitable purposes. Bangladesh J. Sci. Ind. Res. 50(2), 71-76, 2015